EFFECTS OF IRRADIATION ON MEALYBUG Dysmicoccus neobrevipes (Hemiptera: Pseudococcidae) INFESTING ON DRAGON FRUITS - DOAN , THI THE; NGUYEN , THUY KHANH; VO , THI KIM LANG; CAO , VAN CHUNG; TRAN , THI THIEN AN; NGUYEN , HOANG HANH THI (Nuclear Science and Technology, 2011)
Radiotolerance of the mealybug Dymicoccus neobrevipes was investigated with different radiation doses. Development stages and life cycle of D. neobrevipes were determined by rearing under laboratory conditions (Temperature: 28±2°C, Relative humidity: 70±5%, Host: pumpkins). This species has four development stages including 1st, 2nd, 3rd instars and adults and one generation is approximately 30.5 ± 0.3 days. The effect of Co-60 gamma rays on the growth and reproductiveness of D. neobrevipes at different development stages were studied. The preliminary results showed that the radiation resistance of the D. neobrevipes increased with increasing of the development stage. Of the four stages tested, aldults were the most resistant to gamma rays as evidenced by the lowest mortality rate. After 21 days of 300 Gy treatment, the mortality rate of 1st, 2nd, 3rd instars and adults achieved 100%, 96%, 80% and 45%, respectively. Female adults can survive more than three weeks after irradiation at 400 Gy. The results also suggested that the minimum dose of 220 Gy (lower than required dose of 400 Gy) might be applied to control the reproduction of female adults at all growth stages.